Antimicrobial Activity of Ferulic Acid in Indonesian Purple Rice through Toll-like Receptor Signaling - Wijayanti, Ernanin Dyah; Safitri, Anna; Siswanto, Dian; Triprisila, Lidwina Faraline; Fatchiyah, Fatchiyah (UI Scholars Hub, 2021)
Purple rice is a potential source of ferulic acid, which has antimicrobial properties. However, the inhibitory mechanism of ferulic acid on the growth of bacteria, particularly Salmonella and Listeria, has not been elucidated. This study aimed to determine the bioactivity of ferulic acid from purple rice as an antimicrobial agent against Salmonella typhimurium and Listeria monocytogenes using in vitro and in silico analyses. The antimicrobial activity of a purple rice ferulic acid extract was tested using the agar well diffusion method. Its effect on bacterial cells was observed using scanning electron microscopy. Ferulic acid was confirmed to have antimicrobial properties using in silico software to attenuate the binding of bacterial virulence factors (lipoproteins, lipopolysaccharides, and flagellins) to Toll-like receptors (TLRs) and to prevent interactions with peptidoglycans. The purple rice ferulic acid extract inhibited bacterial growth. The inhibitory effects included induction of a biofilm and shrinkage of S. Typhimurium, as well as osmotic lysis of L. monocytogenes. This activity was supported by the ability of ferulic acid to inhibit the binding of bacterial virulence factors with TLRs and block bacterial peptidoglycans. These findings indicate that the purple rice ferulic acid extract acts as antimicrobial, both directly to bacterial cells and indirectly through TLRs. We conclude that ferulic acid from Indonesian purple rice has a biological function as an antimicrobial agent.